2021
DOI: 10.1038/s41589-021-00770-1
|View full text |Cite
|
Sign up to set email alerts
|

LYTACs that engage the asialoglycoprotein receptor for targeted protein degradation

Abstract: Selective protein degradation platforms have afforded new development opportunities for therapeutics and tools for biological inquiry. The first lysosome targeting chimeras (LYTACs) targeted extracellular and membrane proteins for degradation by bridging a target protein to the cation-independent mannose-6-phosphate receptor (CI-M6PR). Here, we developed LYTACs that engage the asialoglycoprotein receptor (ASGPR), a liver-specific lysosomal targeting receptor, to degrade extracellular proteins in a cell type-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
295
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 277 publications
(317 citation statements)
references
References 53 publications
(55 reference statements)
1
295
0
1
Order By: Relevance
“…Site-specific conjugates altered the pharmacokinetic profile of LYTACs in vivo. Whereas nonspecific Ctx-GalNAc conjugates cleared rapidly from plasma before 6 h, site-specific Ctx-GalNAc showed sustained presence for over 72 h (Ahn et al, 2021). This result demonstrated that the clearance regime of a LYTAC can be tuned by varying the number of ligands per antibody.…”
Section: Design Principlesmentioning
confidence: 83%
See 2 more Smart Citations
“…Site-specific conjugates altered the pharmacokinetic profile of LYTACs in vivo. Whereas nonspecific Ctx-GalNAc conjugates cleared rapidly from plasma before 6 h, site-specific Ctx-GalNAc showed sustained presence for over 72 h (Ahn et al, 2021). This result demonstrated that the clearance regime of a LYTAC can be tuned by varying the number of ligands per antibody.…”
Section: Design Principlesmentioning
confidence: 83%
“…We showed internalization of a fluorophore-labeled IgG in a hepatocellular carcinoma (HCC) cell line, HEPG2, mediated by GalNAc-LYTACs. The internalization by a GalNAc-LYTAC was dramatically more efficient than that of an M6Pn-LYTAC in HEPG2 cells, likely due to the higher surface expression of ASGPR compared with M6PR on these hepatocytes (Ahn et al, 2021).…”
Section: Lysosome-targeting Chimerasmentioning
confidence: 95%
See 1 more Smart Citation
“…Studies also revealed that triantenerrary GalNAc (tri-GalNAc) ligands engage ASGPR with higher affinity compared to GalNAc 65 , 66 . Tri-GalNAc ligands are synthesized from peracetylated GalNAc to tri-GalNAc-DBCO in 8 steps, and then are conjugated to azides on non-specifically labeled antibodies 23 . Tang's group directly used the commercially available Tri-GalNAc-COOH.…”
Section: Design and Synthesis Of Lytac And Abtacmentioning
confidence: 99%
“…Bertozzi's group established the first-generation LYTAC, M6Pn-LYTAC, combining the ligand of the cation-independent mannose-6-phosphate receptor (CI-M6PR) with an extracellular protein binder 21 . Pioneering work from research groups of Bertozzi, Spiegel and Tang developed the second-generation LYTAC, GalNAc-LYTAC, with the advantage of cell-specific degradation by engaging the liver-specific asialoglycoprotein receptor (ASGPR) 23 - 25 . Wells and colleagues used the AbTAC, a bispecific antibody, to expand the scope of targeted degradation via transmembrane E3 ligases 22 .…”
Section: Introductionmentioning
confidence: 99%